2019
DOI: 10.3758/s13423-019-01628-3
|View full text |Cite
|
Sign up to set email alerts
|

When masters of abstraction run into a concrete wall: Experts failing arithmetic word problems

Abstract: Can our knowledge about apples, cars, or smurfs hinder our ability to solve mathematical problems involving these entities? We argue that such daily-life knowledge interferes with arithmetic word problem solving, to the extent that experts can be led to failure in problems involving trivial mathematical notions. We created problems evoking different aspects of our non-mathematical, general knowledge. They were solvable by one single subtraction involving small quantities, such as 14-2 = 12. A first experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 25 publications
(29 reference statements)
0
30
1
1
Order By: Relevance
“…We mostly disagree that these conclusions -which indeed contain some elements of insights -can be drawn from the study performed in (Gros et al, 2019) and shall explain why with reference to the broader context of the study. First, we shall briefly summarise its content.…”
Section: Arithmetic Word Problemsmentioning
confidence: 70%
See 4 more Smart Citations
“…We mostly disagree that these conclusions -which indeed contain some elements of insights -can be drawn from the study performed in (Gros et al, 2019) and shall explain why with reference to the broader context of the study. First, we shall briefly summarise its content.…”
Section: Arithmetic Word Problemsmentioning
confidence: 70%
“…Success with regards only to a single correct expected solution of a mathematics WP should therefore not be conflated with the concept of validity that is inherent to mathematical reasoning. A recent study (Gros, Sander, & Thibaut, 2019) addressed this question and concluded that:…”
Section: Arithmetic Word Problemsmentioning
confidence: 99%
See 3 more Smart Citations